Re-contextualizing extra-national policy in the Thai construction industry within the new ASEAN economic community. Issue 1 (2nd January 2016) - Kanjanabootra, Sittimont; Corbitt, Brian
ABSTRACT: Construction stakeholders' perceptions of probable impacts of the implementation of an Association of Southeast Asian Nations (ASEAN) Economic Community (AEC) on practice in the construction industry are analyzed using a policy analysis framework. Implemented in 2015, the AEC is attempting to integrate all economic activities including construction. The construction industry in the AEC countries has been using local laws, regulations, standards, and practices which are not aligned, creating a problem for international construction, engineering, and architecture companies. No new laws or regulations have been foreshadowed or enacted, and there is no consensus about what will be done to address the current anomalies. From interviews, personal stories of senior construction professionals, engaged in construction projects in ASEAN countries, show that the national construction discourse in place currently is what they perceive will remain within an AEC even in a longer timeframe. However, their perception is that change will take considerable time in construction because of a lack of commonality with design and practice standards and existing building codes and different standards in university courses. In the short term, the interviewees believed that there will be no change and the status quo will remain. In the longer term, their belief is that any change will be difficult and contested. The pluralistic nature of multi-state policy necessitates an alternative mode of analysis to understand the inherent complexities and enable theorization of the construction policy process in this type of context.